Effects and safety of Buyang-Huanwu Decoction for the treatment of patients with acute ischemic stroke: A protocol of systematic review and meta-analysis. Issue 23 (5th June 2020) - Jiang, Chao; Xu, Yong-cheng; Zhang, Wen; Pan, Wen; Chao, Xu
Abstract: Background: We designed this study to assess the effects and safety of Buyang-Huanwu Decoction (BYHWD) for the treatment of patients with acute ischemic stroke (AIS). Methods: Electronic databases of Cochrane Library, EMBASE, MEDLINE, CINAHL, PsycINFO, Scopus, Allied and Complementary Medicine Database, VIP Database, and China National Knowledge Infrastructure will be comprehensively and systematically searched from initial time of each electronic database to the present without limitations of language and publication status. Randomized controlled trials on BYHWD alone against any other interventions for the treatment of AIS will be included. All process of study selection, data collection, and methodological quality assessment will be independently undertaken by 2 investigators. Cochrane risk of bias tool and RevMan 5.3 software will be utilized for the performance of methodological quality assessment and statistical analysis, respectively. Results: This study will summarize most recent high quality evidence on investigating the effects and safety of BYHWD alone against any other interventions for the treatment of patients with AIS. Conclusions: The findings of this study will provide helpful evidence for the clinical practice for patients with AIS using BYHWD, as well as the relevant future researches. Study registration number: INPLASY202040169.